Macroscopic illustration of Zn evaporation during liquid phase sintering of Cu–28Zn prepared from prealloyed powder. (29th May 2015) - Azadbeh, Maziyar; Danninger, Herbert; Mohammadzadeh, Ahad; Gierl-Mayer, Christian
Abstract : The formation of a liquid phase during sintering of prealloyed Cu–28Zn powder is potentially attractive for densification, but the effect of gravity results in graded densification which tends to result in heterogeneous cross-sections. The formation of a necklace structure along grain boundaries due to the accumulation of liquid phase with high Zn content, especially at higher temperatures, is also of interest. Evaporation of zinc is another essential feature to consider, since loss of Zn during sintering can influence strongly the mechanical properties of brass products. A macroscopic visualisation of Zn evaporation has been achieved using a copper substrate placed within the gas stream near the sample. FEGSEM observation and XRD analysis of the deposited white mass revealed the formation of nanocrystalline ZnO as a consequence of Zn evaporation. It is proposed that this method could usefully show the evaporation of other alloying elements during sintering of similar alloys.